Pattern of anemia in geriatric patients- A hospital based prospective study - Roma Singh; Bindu Singh Gaur (International Journal of Medical Research and Review, 2016)
Introduction: Anaemia is common in elderly age group and is overlooked as the symptoms such as fatigue, weakness, shortness of breath may be attributed to the ageing process itself but decline in the haematological parameter with age is not necessarily as a result of normal aging. Low Hb is a powerful prognostic marker for multiple adverse outcomes in the elderly. Clinicians should be alerted to the increased risk of morbidity, hospitalization and mortality in the elderly associated with anemia.Aim of study: To evaluate the prevalence of geriatric anaemia, morphological pattern of geriatric anaemia and to find its commonest morphological pattern amongst the geriatrics in hospitalized patients.Material and Methods: A hospital based observational prospective study of 6 months from August 2015 to January 2016 conducted in haematology section of Pathology department at L. N. Medical college and RC and attached J. K. Hospital Bhopal, M.P. in which 200 hospitalized geriatric patients both male and female above the age of 60 years were included and were evaluated for the prevalence of anemia in both the genders along with morphological pattern of anemia.Results: Prevalence of anemia in geriatrics including both sexes is 69% (n=138/200). In female group 73.68% (56/76) and in Male group there were 66.12% (82/124) anaemic cases. Most common morphological pattern is normocytic normochromic anaemia i.e 37.68%.Conclusion: Study of various morphological patterns of anaemia helps in guiding aetiology of anaemia and thus directing towards the further required investigations facilitating the choice and implementation of effective therapy.